The development and future-proofing of treatment wetlands as nature-based solutions in the UK water sector: Southern Water case studies - Phuyal, Pramila Bhandari; Edevane, Joff; Lyu, Tao (MDPI, 2026)
Treatment wetlands (TWs) are increasingly deployed as nature-based solutions for water and wastewater management due to their cost-effectiveness, operational simplicity, and provision of wider ecosystem benefits. The UK has been at the forefront of TW application since the 1980s. This study evaluated their development and performance within Southern Water, a water utility in the UK. In total, 35 sewage treatment sites have incorporated TWs since 1991, primarily for tertiary treatment and stormwater overflow control. Performance data were available for 16 sites, comprising 14 horizontal subsurface flow (HSSF) and two surface flow (SF) wetlands. HSSF wetlands achieved substantial reductions in TSSs (up to 97%), NH4+ (up to 99%), and BOD5 (up to 92%). The COD removal showed more variance (0–62%) in the studied sites. In contrast, SF wetlands provided moderate reductions in TSSs (17–79%) and COD (36–67%) but were less effective for NH4+ and BOD5 (14–65%). The TWs operated by Southern Water currently serve more than 100,000 people and illustrate the expanding role of such systems in meeting wastewater treatment needs. However, challenges and further research are needed, including risks of media clogging, the evaluation of emerging micropollutants treatment, and inconsistent maintenance. To address these, the study highlights opportunities for innovation through hybrid and aerated designs, advanced monitoring, and a more detailed understanding of plant–microbe interactions. The findings emphasise both the potential and future research needs of TWs and support their continued integration into wastewater management strategies under evolving environmental and regulatory pressures.
This article belongs to the Special Issue Biological Treatment Processes for Wastewater: Latest Advances and Prospects
Keywords: 4104 Environmental Management; 40 Engineering; 41 Environmental Sciences; 4004 Chemical Engineering; 4011 Environmental Engineering; 6 Clean Water and Sanitation; constructed wetlands; green infrastructure; storm overflows; UK water industry; wastewater treatment